First-in-Human Evaluation of Positron Emission Tomography/Computed Tomography With [18F]FB(ePEG12)12-Exendin-4: A Phase 1 Clinical Study Targeting GLP-1 Receptor Expression Cells in Pancreas - Fujimoto, Hiroyuki; Fujita, Naotaka; Hamamatsu, Keita; Murakami, Takaaki; Nakamoto, Yuji; Saga, Tsuneo; Ishimori, Takayoshi; Shimizu, Yoichi; Watanabe, Hiroyuki; Sano, Kohei; Harada, Norio; Nakamura, Hiroshi; et al. (Frontiers in Endocrinology, 2021)
Pancreatic β cell mass (BCM) has a central importance in the pathophysiology of diabetes mellitus. Recently, pancreatic β cell specific imaging, especially positron emission tomography (PET) with exendin-based probes, has emerged for non-invasive evaluation of BCM. We developed a novel exendin-based probe labeled with fluorine-18, [18F]FB(ePEG12)12-exendin-4 (18F-Ex4) for PET imaging. We subsequently conducted a first-in-human phase 1 study of 18F-Ex4 PET/computed tomography (CT) and investigated the safety and utility of visualizing the pancreas. Six healthy male subjects were enrolled in this study. A low dose (37.0 MBq) of 18F-Ex4 PET/CT was administered (1st cohort: n = 2) and subsequently a higher dose (74.0 MBq) was administered (2nd cohort: n = 4). 38.6 ± 4.8 and 71.1 ± 4.8 MBq of 18F-Ex4 were administered in the 1st and 2nd cohorts, respectively. No serious adverse events were observed in both groups. Only one participant in the 1st cohort showed transient hypoglycemia during the PET scans. 18F-Ex4 PET/CT successfully visualized the pancreas in all participants. The mean standardized uptake value of the pancreas were found to be higher than the surrounding organs, except for the bladder and kidneys, during the observation. Dosimetry analyses revealed the effective systemic doses of 18F-Ex4 as 0.0164 ± 0.0019 mSv/MBq (1st cohort) and 0.0173 ± 0.0020 mSv/MBq (2nd cohort). 18F-Ex4 PET/CT demonstrated the safety and utility for non-invasive visualization of the pancreas in healthy male subjects. 18F-Ex4 is promising for clinical PET imaging targeting pancreatic β cells.